PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA BLOOKET TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS V SEKOLAH DASAR - Aulya Ramadhani; Asrial; Faisal Hidayat, Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Problem Based Learning (PBL) model assisted by Blooket media on elementary school students’ mathematical critical thinking skills. The research employed a quantitative approach using a quasi- experimental design with a nonequivalent control group design. The population consisted of all fifth-grade students of SD Negeri 27/IX Sebapo in the first semester of the 2024/2025 academic year, totaling 45 students. The sample was divided into two classes: class VA as the experimental group and class VB as the control group. Data were collected through a mathematical critical thinking skills test administered in the form of pretest and posttest. The data were analyzed using normality tests, homogeneity tests, and an independent sample t-test. The results indicate a significant difference in mathematical critical thinking skills between students taught using the PBL model assisted by Blooket media and those taught using conventional learning methods. Therefore, it can be concluded that the implementation of the Problem Based Learning model assisted by Blooket media has a positive effect on elementary school students’ mathematical critical thinking skills.